ANALISIS PELAYANAN PUBLIK PEMERINTAHAN DESA TLANAK KECAMATAN KEDUNGPRING KABUPATEN LAMONGAN - Saputri, S.Pd., M.H., Ernia Duwi (Universitas 17 Agustus 1945 Surabaya, 2018)
Public Service Analysis of Village Tlanak Support of Lamongan District. The purpose of this research is to know the quality of Public Service of Village Government of Tlanak Kedungpring District of Lamongan Regency, to know the supporting and inhibiting factors and solution of Public Service of Village Government ofÂ Tlanak Kedungpring District ofÂ Lamongan Regency and to know the implementation of Good Governance in Public Service of Village Government of Tlanak Kedungpring District of Lamongan Regency. The type of this research is non-doctrinal (sosiologis) legal research. Non-doctrinal method is a type of scientific study with the intention just to learn just and not to teach something doctrine. The research method used is research method with qualitative analysis. The results of this study concluded that the quality of Public Service Village Tlanak Kedungpring District Lamongan through Programs, policies, and attitudes is Services Open, easy and accessible by all parties who need and provided adequate and easy to understand, can be accounted for in accordance with the provisions of legislation - invitation, inhibiting the public service of Tlanak village administration of Kedungpring Sub-district of Lamongan Regency is seen in the condition of society which still have a lot of parochial political culture. The solution of inhibiting factor of public service in Tlanak Village, Kedungpring Sub-district, Lamongan Regency by strengthening service system, improving professionalism of each employee, conducting public awareness program to help dissemination and comprehension of information to society about matters related to service activity and giving sanction that is firm. The village government of Tlanak Kedungpring District of Lamongan Regency has not fully implemented the Good Governance principles in the implementation of the village government's tasks, functions, authorities, rights, and obligations in terms of planning, service, implementation of village development, especially those related to village governance.Keywords: Quality Analysis of Public Service, Good Governance.